Aid for trade and the liberalization of trade - Hoekstra, Ruth (2012)
Considers the debate on aid for trade and posits that the delivery of AFT is a precondition for trade reform trade-enhancing rule-making in developing countries and that it may cushion adjustment problems to trade liberalization.